Data Mining in Auditing: Challenges and Opportunities - Aditya Arisudhana; Khaula Lutfiati Rohmah (Universitas Respati Yogyakarta, 2023)
Audit is a process of evaluation of a subject matter with a view to express an opinion on whether the subject matter is fairly presented carried out by an independent party. Assessment of the fairness of financial statements is very important because of the conflict of interest between the preparers of financial reports and stakeholders. The audit usually uses sampling to obtain data related to the fairness assessment. The auditor uses sampling because of time and cost constraints. Sampling also has a risk that can lead to errors in assessing the fairness of financial statements. Therefore we need a method that can improve accuracy in data collection and processing, for example data mining. Data mining is a method that can be used to collect and process data more quickly and accurately. The use of data mining techniques that may develop in the future can have an impact on the audit process. Data mining in audits will be both an opportunity and a challenge for auditors in the future